Comparison of the transport of QX-314 through TRPA1, TRPM8, and TRPV1 channels - Nakagawa, Hiroshi (Dove Medical Press, 2013)
BACKGROUND: It has been demonstrated that N-ethyl-lidocaine (QX-314) can target the transient receptor protein vanilloid 1 (TRPV1) nociceptors when coadministered with capsaicin, resulting in a selective block of the nociceptors. Capsaicin is problematic in therapeutic use because it induces firing of nociceptors. The present study aimed to search for substitutes for capsaicin. We also examined the transportability of QX-314 into nociceptive neurons, through the pores of transient receptor potential ankyrin 1 (TRPA1), transient receptor potential melastatin-8 (TRPM8), and TRPV1. METHODS: To investigate the effect on TRPA1, injections of a vehicle, allyl isothiocyanate (AITC), QX-314, or AITC/QX-314 were made into the hind paws of rats. The effects of menthol and capsaicin on the opening of TRPM8 and TRPV1 were also examined and compared with the potency of QX-314. To examine inhibition of the antinociceptive effect by capsaicin/ QX-314, capsazepine (50 μg/mL; 10 μL) was injected 30 minutes prior to capsaicin/QX-314 (10 μL) injection. Thermal sensitivity was investigated by the Hargreaves method. 5(6)-carboxyfluorescein (FAM)-conjugated QX-314 was used as a tracer to examine how many and which kind of dorsal root ganglia accumulate this molecule. QX-314-FAM, capsaicin/QX-314-FAM, AITC/QX-314-FAM, and menthol/QX-314-FAM were injected into the paw. Two weeks after injections, dorsal root ganglia were removed and sectioned with a cryostat. RESULTS: The capsaicin/QX-314 group induced longer withdrawal-response latency at 60 to 300 minutes after injection than the control. Both menthol only and menthol/QX-314 injections showed analgesia 10 to 60 minutes after injection. No significant difference was seen between the capsazepine/capsaicin/QX-314 group and the vehicle group. The fluorescence in small- and medium-sized neurons was conspicuous in only the dorsal root ganglia injected with capsaicin/ QX-314-FAM. CONCLUSION: These results indicate that TRPA1 and TRPM8 are ineffective in the transport of QX-314 compared with TRPV1.